Work-related stress disorders: variability in clinical expression and pitfalls in psychiatric diagnosis - Buselli, Rodolfo; Veltri, Antonello; Baldanzi, Sigrid; Bozzi, Silvia; Marino, Riccardo; Chiumiento, Martina; Dell'Osso, Liliana; Cristaudo, Alfonso (La Medicina del Lavoro, 2016)
Background: Putative occupational stress-related psychiatric disorders are Adjustment Disorders (AD) and Post-Traumatic Stress Disorder (PTSD). Mood Disorders (MD) are not excluded but are unlikely to be identified as occupational diseases. The differential diagnosis between AD and MD is not easy and is based on strict categorical criteria. Objectives: The aim of this study was to explore differences in personality and mood spectrum symptoms among workers investigated for occupational stress suffering from AD or MD. Methods: Sixty-two patients with AD and 43 with MD were recruited and evaluated by means of rating scales for psychosocial occupational risk and work-related stress (WHS, CDL, OSQ), for sleep disturbances (PSQI), for personality disorders (SCID-II) and for mood spectrum symptoms (MOODS-SR). Results: The diagnostic groups did not differ for WHS, OSQ and PSQI scores. The duration of exposure to stressful/adversative work situations was significantly higher in the MD group (p=0.03). Positive family psychiatric history (p=0.005), personality disorders (p=0.009) and pathological personality traits (p<0.0001) were significantly more frequent in the MD group. The MOODS-SR questionnaire total score (p=0.019) and the manic component score (p=0.001) but not the depressive score were significantly higher in the MD group. Conclusions: The present study suggests that positive family psychiatric history, pathological personality traits and spectrum manic symptoms represent markers of vulnerability and low resilience for workers exposed to occupational stress. These characteristics could weaken the etiological relationship between work-related stress and an initial major depressive episode when it is under investigation as a possible occupational disease.